88.2k views
1 vote
Directions: Transform the following equations into standard form.

1. x2 + 2x = -1
2. 4 + x2 = 7x
3. x2 - x = 1
4. x2 + 9x = 10
5. 4x + 3 = x2
6. x2 + 5x +5
7. 2x5 + 7x = 3x
8. x2 = 3x + 8
9. x(x + 3) = 1
10. x2 - 3x = -2
11. y2 - 7y = -6
12. z2 - 5z = -4

User MayankGaur
by
4.6k points

2 Answers

5 votes

Answer: ^^

1. x2 + 2x + 1 = 0

2. x^2 - 7x + 4 = 0

3. x^2 - x - 1 = 0

4. x^2 + 9x - 10 = 0

5. -x^2 + 4x + 3 = 0

6. x^2 + 5x - 5 = 0

7. 2x^5 + 7x - 3 = 0 or 2x^5 + 4x = 0

8. x^2 - 3x - 8 = 0

9. x^2 + 3x - 1 = 0

10. x^2 - 3x + 2 = 0

11. y^2 - 7y + 6 = 0

12. z^2 - 5z + 4 = 0

Explanation:

:)

User Igor Goyda
by
5.4k points
2 votes

The standard form is:

  • ax² + bx + c = 0

Convert each equation:

1. x² + 2x = -1 add 1 to both sides

⇒ x² + 2x + 1 = 0

2. 4 + x² = 7x add - 7x to both sides and rearrange

⇒ x² - 7x + 4 = 0

3. x² - x = 1 add - 1 to both sides

⇒ x² - x - 1 = 0

4. x² + 9x = 10 add - 10 to both sides

⇒ x² + 9x - 10 = 0

5. 4x + 3 = x² add -4x - 3 to both sides

⇒ x² - 4x - 3 = 0

6. x² + 5x = 5 add -5 to both sides

⇒ x² + 5x - 5 = 0

7. 2x² + 7x = 3 add -3 to both sides

⇒ 2x² + 7x - 3 = 0

8. x² = 3x + 8 add -3x - 8 to both sides

⇒ x² - 3x - 8 = 0

9. x(x + 3) = 1 distribute and add - 1 to both sides

⇒ x² + 3x - 1 = 0

10. x² - 3x = -2 add 2 to both sides

⇒ x² - 3x + 2 = 0

11. y² - 7y = -6 add 6 to both sides

⇒ y² - 7y + 6 = 0

12. z² - 5z = -4 add 4 to both sides

⇒ z² - 5z + 4 = 0

User Bilal Maqsood
by
4.9k points